Arab Uprisings, Armed Forces, and Civil–Military Relations. (January 2013) - Lutterbeck, Derek
Since late 2010, an unprecedented wave of protests demanding greater political freedoms, and in several countries even regime change, has swept across much of the Arab world. In Tunisia, Egypt, and Libya, long-standing autocrats have been toppled, and in other countries of the region seemingly well-established authoritarian regimes also appeared increasingly shaky in the face of growing opposition movements. The aim of this article is to examine the role of the armed forces in these popular uprisings. While military forces have been key actors in these Arab uprisings, they have responded quite differently across the region to prodemocracy movements, ranging from openness to protest movements, to internal fracturing, to firm support for the regime in power. This article argues that these differences can be explained with reference to different forms of civil–military relations and different characteristics of the military apparatus. It claims in particular that the degree of institutionalization of the armed forces and their relationship to society at large can account for the divergent responses to pro-reform movements.